Les Haploniscidae (Crustacés Isopodes Asellotes) de l'Atlantique. Description de huit espèces nouvelles - Chardy, Pierre (Museum National d'Histoire Naturelle, 1974)
Eight new species from Atlantic deep sea bottom are described in this work : Haploniscus foresti, Haploniscus monodi, Haploniscus reyssi, Haploniscus obtusifrons, Haploniscus myriamae, Haploniscus furcatus, Antennuloniscus dilatatus, Hydroniscus vandeli. Additional description of Haploniscus unicornis Menzies, 1962, based on a male specimen, is included. Biogeographical considerations, based on the 48 species of Haploniscidae recorded from Atlantic bottom, suggests a high rate of regional endemism (concerning this family) between North and South Atlantic ocean. [NOT CONTROLLED OCR] Description de huit espèces nouvelles d'Isopodes Asellotes, appartenant A la famille des Haploniscidae, récoltées sur la plaine abyssale de l'Atlantique : Haploniscus foresti, Haploniscus monodi, Haploniscus reyssi, Haploniscus obtusifrons, Haploniscus myriamae, Haploniscus furcatus, Antennuloniscus dilatatus, Hydroniscus vandeli. Haploniscus unicornis Menzies, 1962, fait l'objet d'un complément de description, établi sur un spécimen mâle. Des considérations biogéographiques, fondées sur la répartition des 48 espèces d'Haploniscidae provenant de la plaine abyssale atlantique, font apparaître un endémisme marqué, dans cette famille, entre les parties nord et sud de l'océan Atlantique. [OCR NON CONTRÔLE]